Clean Water Empowerment in Waur Village, Kei Besar Subdistrict, Southeast Maluku Regency - Riry, Johan; Jeujanan, Klementina; Leuwol, Ferdinand Salomo (JENDELA PENGETAHUAN, 2024)
This study aims to evaluate and provide recommendations regarding the empowerment of clean water in Waur Village, Kei Besar District, Southeast Maluku Regency. Although Waur Village has a significant population of 366 households or 1,569 people, efforts by the local government and relevant private institutions to manage clean water are still minimal. This study focuses on three main water sources, namely Faderni, Metan Evav, and Snalut, which often experience drought during the dry season, making it difficult for the community to obtain clean water. The methodology used includes field observations, interviews with respondents, and water sample testing conducted by the Health and Calibration Laboratory Center of Maluku Province. The results of the study show that the three water sources do not yet have adequate facilities, with leaking and uncovered reservoirs, and there is no empowerment process such as water sampling for feasibility testing or health socialization programs related to water management. Water sample tests indicate that water from Faderni, Metan Evav, and Snalut springs has good odor and taste parameters (No Odor and No Taste) and a color level that is still suitable for consumption. This study is expected to be a consideration for relevant parties in making more effective and efficient efforts to empower clean water in Waur Village